Passing and shooting in football: Playing with the ball… and the others - Vicente, A.; Lopes, H.; Fernando, C. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: Winning in football is about scoring more goals than the opponent. To do so, players must master a set technologies that, together with other technical, tactical, psychological and physiological (among others) factors will allow them to be successful. Although it is common to believe that in football the key is to play with the ball, master the ball at high speeds and in small spaces, studies that we have been developing in recent years on isolated situations (e.g. Vicente et al. 2015) showed that there is time relations with the opponents that players must not ignore to succeed. The aim of this study was to verify whether a correlation exists between the velocity of the stimulus in passing and shooting situations in football and the attacking and defending player`s responses. METHODS: We`ve used a software (MeSiR2.2) designed to measure the relation between the velocity of the stimulus and the time to respond it. Four tests were used: Test 1 had a goalkeeper that moved from the center of the goal to each side (left or right) at different velocities (1 and 3 m/s) randomly; Test 2 had a striker that kicked a ball from the penalty kick spot to each side of the goal (left or right) at different ball velocities (±40km/h and ±90 km/h) randomly; Test 3 consisted on a defender that moved 3 meters in a real football field to each side (left or right) at different velocities (5 and 1 m/s) randomly; Test 4 consisted on a player with a ball that kicked it to the left or right at different ball velocities (±10km/h and ±50 km/h) randomly. 40 university football players and 25 semi-professional footballers had to perform each test for 20 trials and respond to each situation by moving their body towards the ball side (tests 2 and 4) or shooting a ball in the opposite direction to the movement of the player (tests 1 and 3). RESULTS: From the 5200 trials performed from the 4 tests, results showed that players took the right decision in 83% of the situations. Data also showed that for the fastest stimulus in tests 2 and 4 the average response time was also higher (test 2=378ms / test 4=399ms) than the slowest stimulus situations (test 2=427ms / test 4=473ms). The same trend was obtained on tests 1 and 3. Participants tended to kick the ball at lower speeds in response to slower opponents movements (73% in test 1 and 68% in test 3) than in higher opponents movements. DISCUSSION: Data showed that the stimulus velocity tend to influenced the response and the time to respond. As the stimulus was faster or slower the response was also faster or slower. The results tend to corroborate previous studies and other ecological studies we`re still performing. This suggest that in passing and shooting situations in football, where players are permanently exchanging stimulus with opponents and teammates, players must be prepared to relate with the opponents and teammates being aware that they can influence their actions and response times to take advantage and increase success chances.